PERPADUAN ARSITEKTUR ART DECO DAN INTERNATIONAL STYLE PADA BANGUNAN GAIA HOTEL BANDUNG DAN PADMA HOTEL - Grasilla Hartono, Bianca; Prijotomo, Josef (Jurnal Riset Arsitektur, 2025)
Abstract - Modernization gradually leads to the development of modern architecture, leaving local architecture behind. Consequently, modern architecture begins to overshadow the existence of Indonesian local architecture. Thus, there’s an urgent need for a fusion of the local and modern elements in architecture.Notably, through observation, the distinctive Art Deco context is a strong character in Bandung. Moreover, Bandung is ranked 9th in the City Of Art Deco in The World. During the modern architecture era, international style was developed as one of the architectural styles. This style has been appreciated and favored by the public up to this day because it is considered to follow the development of the industry and technology while remaining functional. This research method is descriptive qualitative and analytical methods. The first step is to identify the building designs, followed by identifying the Art Deco and international style characteristics in the buildings and the fusion. Theoretically and practically, this research is expected to provide additional insights for both the author and readers regarding Bandung's Art Deco heritage, thereby contributing to the field of architectural knowledge In general, the result reveals that both hotels exhibit Art Deco and international style features in their designs. In terms of percentage, The Gaia Hotel Bandung has a dominance of 46.7% classified as Modern Art Deco. Meanwhile, Padma Hotel Bandung has a percentage of 47.02% classified as Modern Art Deco. It can be observed that Padma Hotel has a higher Art Deco percentage. Keywords: fusion, art deco, international style, dominance